Continental-scale assessment reveals inadequate monitoring for threatened vertebrates in a megadiverse country. (July 2019) - Scheele, Ben C.; Legge, Sarah; Blanchard, Wade; Garnett, Stephen; Geyle, Hayley; Gillespie, Graeme; Harrison, Perter; Lindenmayer, David; Lintermans, Mark; Robinson, Natasha; Woinarski, John
Abstract: Monitoring threatened species is essential for quantifying population trends, understanding causes of species' declines, and guiding the development and assessment of effective recovery actions. Here, we provide a systematic, continental-scale evaluation of the extent and quality of monitoring for threatened species, focussing on terrestrial and freshwater vertebrates in Australia. We found marked inadequacies: one in four threatened taxa are not monitored at all; for taxa that are monitored, monitoring quality, as assessed across nine metrics, was generally low. Higher quality monitoring was associated with policy recognition, in the form of species recovery plans, and for species having a more imperilled conservation status. Across taxonomic classes, the proportion of species monitored was highest for mammals and then birds, whereas monitoring quality was greatest for birds. Improving monitoring quality requires setting clear objectives, direct integration with management, incorporating explicit management triggers, long-term resourcing, and better communication and accessibility of monitoring information. While our results revealed that overall monitoring efforts are inadequate, the positive relationship between improved monitoring outcomes and national policy support highlights that, when resources are available, good monitoring outcomes can be achieved. Quality monitoring programs for threatened species, and biodiversity more generally, should be recognized as vital measures of a nation's progress, analogous and complementary to more widely-used economic and human health indicators. Highlights: Threatened species monitoring is markedly inadequate. Mammals are most commonly monitored, while bird monitoring is higher quality Fish and reptiles receive least monitoring. Inadequate monitoring compromises conservation efforts. Improved monitoring outcomes are associated with national legislative support.